Look what i can play! a lift the flap book - Siewert, Pauline (Windmill Books New York, 2010)
This lively book introduces children to different games and play activities. With colorful illustrations and interactive prompts, it encourages kids to engage in imaginative play and explore various ways to have fun with friends. It's a great way to foster creativity and social skills through play.